Stratifying measuring requirements and tools for cloud services monitoring - Carvalho, Paulo (2019)
Monitoring plays an essential role in the management and engineering of today’s communication networks. Facing paradigms such as cloud computing and network virtualization, the challenges of monitoring are even more demanding, attending to the variety and dynamics of services and resources involved. The lack of standards regarding cloud services monitoring makes even more difficult to reach a common ground on how to assess these services. In this context, this paper takes a high-level stratified view of the problem to clarify and systematise the involved pieces in cloud services monitoring, from the physical/virtual infrastructure to the customer/provider layer. In each layer, relevant measuring requirements and metrics are discussed, following existing guidelines for the evaluation of performance, reliability, security, and service level agreements fulfilment. In addition, representative cloud services in the market are aggregated per service model and relevant monitoring tools are surveyed and mapped into the proposed functional layers. The present study is a step forward contributing to achieve a more modular, flexible and consensual view to cloud services monitoring.